The use of Standardized Precipitation Index values (SPI) and MODIS vegetation indices to assess drought of steppe regions, Algeria - Boudjemline, Fouzia; Benlabiod, Denidina (Technium Social Sciences Journal, 2022)
Drought events were assessed using remote sensing index MODIS (MODerate resolution Imaging Spectroradiometer) and Standardized Precipitation Index (SPI) over the steppe regions of Algeria between 2000 and 2012. In this study, the Vegetation Condition Index (VCI) and Temperature Condition Index (TCI) were determined from Moderate Resolution Imaging Spectroradiometer (MODIS) sensor. The VCI (Vegetation Condition Index) was based on the Normalized Difference Vegetation Index (NDVI) datasets. The TCI (Temperature Condition Index) was derived from land surface temperature (LST) datasets. The VCI and TCI were then combined to calculate the Vegetation Health Index (VHI). Also, the one-month Standardized Precipitation Index (SPI) data from rainfall stations in the study area was calculated. The results show that years of normal condition (least drought) were year 2006, 2009, 2010 and 2012. However, all indices recorded a drought with different classes for 2000, 2001, 2002, 2003, 2004, 2005, 2007,2008 and 2011 can be considered unusual conditions. According to the results obtained from this study, a large part of the study area is located in severe of drought classes that likely is related to the rainfall reduction and topographic characteristics of the area and poor vegetation, which need more attention to water resource management in this region.